Influence of different rainfall patterns and soil water content on hydrological processes in small watersheds - Li, Chaochao; Li, Chenglu; Bao, Shuping; Li, Mingyang (Frontiers in Environmental Science, 2023)
Due to climate and underlying surface changes, flash floods occur frequently in northwest China, and the extreme rainstorm weather and flash floods along the eastern foot of Helan Mountain are increasing. By constructing a hydrological model to simulate ten historical mountain flood events in the Suyukou watershed of the eastern foot of Helan Mountain, this study explores the constitutive relationship between rainfall and flood, evaluates accuracy, and analyzes errors. Six characteristic rain patterns were designed based on three parameters representing the position of rainfall peaks and the trend characteristics of rainfall, using 63 actual rainfall processes with a duration of 6 hours selected from the rainfall stations of Suyukou watershed. Early warning indicators under different conditions were carried out based on the set of rain patterns. The research results indicate that eight out of the ten simulated floods have passed the qualification test and the simulation results are good. The HEC-HMS hydrological model is suitable for simulating mountain floods in small watersheds and can provide good support for the simulation and early warning of mountain flood disasters. Designing a rain pattern set based on actual data has put forward higher requirements for mountain flood warning and forecasting, making the warning more in line with the local actual situation and greatly improving the effectiveness of warning and forecasting.